Differential Protein Expression Patterns of HOXA13 and HOXB13 Are Associated with Bladder Cancer Progression - Chin, Fee-Wai; Huzlinda, Hussin; Chau, De Ming; Ong, Teng Aik; Rosna, Yunus; Azad Hassan, Abdul Razack; Khatijah, Yusoff; Chan, Soon Choy; Abhi, Veerakumarasivam * (MDPI, 2023)
Bladder cancer is a common urological cancer and has the highest recurrence rate of any cancer. The aim of our study was to profile and characterize the protein expression of homeobox A13 (HOXA13) and homeobox B13 (HOXB13) genes in Malaysian bladder cancer patients. The protein expression of HOXA13 and HOXB13 in formalin-fixed paraffin-embedded (FFPE) bladder cancer tissues was determined by immunohistochemistry (IHC) analysis. The association between HOXA13/HOXB13 protein expression and demographic/clinicopathological characteristics of the bladder cancer patients was determined by chi-square analysis. Approximately 63.6% of the bladder cancer tissues harbored high HOXA13 expression. High HOXA13 expression was significantly associated with non-muscle invasive bladder cancer, lower tumor grade, higher number of lymph node metastases, and recurrence risk. In contrast, low HOXB13 expression (including those with negative expression) was observed in 71.6% of the bladder cancer tissues analyzed. Low HOXB13 expression was significantly associated with muscle-invasive bladder cancer, higher tumor stage, tumor grade, and metastatic risk. Both HOXA13 and HOXB13 protein expression were found to be associated with bladder tumorigenesis. The putative oncogenic and tumor suppressive roles of HOXA13 and HOXB13, respectively, suggest their potential utility as biomarkers in bladder cancer.